Triathlon cycle-run transition: seated versus alternating seated and standing cycling - Jensen, R. L.; Cunniffe, B.; Harrison, A. J.; Phelan, B.; Shafat, A. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
Nine experienced triathletes completed two trials of a cycle to run transition. During the last three minutes of a 30 minute cycling bout (at power output equal to lactate threshold) subjects either remained seated (SEAT), or alternated seated and standing cycling (30 s at a time) (ALT). Minimum and maximum knee angle and stride frequency were obtained at the end of a three minute control run (C) and at minutes 0, 2, & 4, of running after cycling transition. The only difference found by Two-Way Repeated Measures ANOVA (condition X minute) was that C was significantly different than minute 0 of the transition for stride frequency (p <0.05). The findings of the current study indicate that there is a change in stride length following cycling, however, the ALT strategy did not change the kinematic variables during running following cycling when compared to SEAT.